The beginnings of medieval romance : fact and fiction, 1150-1220 - Green, D. H. (Dennis Howard), 1922-2008 (Cambridge studies in medieval literature, 2002)
Until the twelfth century writing in the western vernaculars dealt almost exclusively with religious, historical and factual themes, but the second half of the twelfth century saw the emergence of a new genre consciously conceived as fictional, the romance. Dennis Green explores how and why this shift occurred.